If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 2 = 3x + 6 Reorder the terms: 2 + 8x = 3x + 6 Reorder the terms: 2 + 8x = 6 + 3x Solving 2 + 8x = 6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 2 + 8x + -3x = 6 + 3x + -3x Combine like terms: 8x + -3x = 5x 2 + 5x = 6 + 3x + -3x Combine like terms: 3x + -3x = 0 2 + 5x = 6 + 0 2 + 5x = 6 Add '-2' to each side of the equation. 2 + -2 + 5x = 6 + -2 Combine like terms: 2 + -2 = 0 0 + 5x = 6 + -2 5x = 6 + -2 Combine like terms: 6 + -2 = 4 5x = 4 Divide each side by '5'. x = 0.8 Simplifying x = 0.8
| 4b-15+8b=-39 | | (x+2)(x)(4)=396 | | -2(4y-2)=4 | | 36a^2-60a+25=0 | | -29-9x=52-6x | | -7-4m-16=23 | | 16x+8=-14x+12 | | 3x+4x=0 | | 16a^4+20a^3-50a^2=0 | | 6(y+3)=4(y+9) | | -2(4y-4)=3 | | 5m-(m+5)=11 | | -4x-89=12x+183 | | y=x^2-10x+14 | | 6(3x-6)=3(6x+3) | | 7w-3w+43=-15 | | -2(2y-5)=3 | | 3+2y-1=7y+6-4y | | -x-64=69+6x | | 2x+(2x+2)=46 | | 2(y-1)=5y+5 | | 3x^2-33x-27=0 | | 16-4e=2e | | x-2x=x | | xy+7x+2y+14=0 | | 3t+4t=35 | | 30=8-11y | | -141+x=-11x+99 | | 4x-3=93 | | x+12=2x+4 | | log^9(-11x+2)=log^9(x^2+30) | | a^6+9a^4b^2=0 |